UPAYA INDONESIA DALAM MENCAPAI RESOLUSI FEMALE PEACEKEEPERS DI PBB TAHUN 2020 - Ilham Bintang; Retno Susilowati; Muchammad Yustian Yusa (Andalas Institute of International Studies, 2022)
The United Nations (UN) has scheduled the involvement of women in world defense defense missions. However, the fact is that the number of women's participation in world peacekeeping forces is still minimal and continues to decline every year. Departing from this problem, Indonesia initiated the adoption of the Female Peacekeepers Resolution in 2020. This study looks at how Indonesia's efforts to resolve the female peacekeepers resolution through integrative negotiation theory with dimensions of expand pie and dual concern. This study uses qualitative research methods with data collection methods library analysis. The result of this research is an integrative negotiation effort through expansion stages including how Indonesia became a non-permanent member of the UN Security Council, an agenda that focuses on increasing the role of women through the submission of peacekeeping resolutions. Then in the dual concern stage, Indonesia submitted a draft resolution, garnered support from other countries to participate in submitting the resolution, informal negotiations and the voting process. So that the draft was approved by all member states of the security council which was later adopted into a new one with number 2538 of 2020.